Rapid densification of nanocrystalline zirconia: Pressureless versus pressure-assisted spark plasma sintering - Andraž Kocjan; Nikhil Bhootpur; Aljaž Iveković; Mirva Eriksson (Open Ceramics, 2024)
Spark plasma sintering (SPS) is the most straightforward way to rapidly sinter nanoceramics, but the applied pressure prevents sintering of additively manufactured ceramics. Therefore, fast firing techniques such as “pressureless” SPS and ultra-fast high-temperature sintering, based on intense thermal radiation, are gaining interest. Here we compare pressure/current-assisted and pressureless SPS techniques for the rapid heating (∼300 °C/min, 5 min) of nanocrystalline zirconia with high sintering activity. The applied pressure and current indeed contributed to the lowestr temperatures needed for full densification of nanocrystalline zirconia, retaining very fine grain size, but also induced tetragonal phase transformations in the final sintering stages. When the radiative heat transfer was “decoupled” (pressureless SPS), a pronounced temperature difference between graphite crucible wall and simulated specimen temperature along with non-steady-state conditions during dwell were observed. Nevertheless, high heating rates facilitated fine and dense microstructures even in the absence of pressure/current.